A Prediction System of Dengue Fever Using Monte Carlo Method - Roziqin, Mochammad Choirur; Basuki, Achmad; Harsono, Tri (EMITTER International Journal of Engineering Technology, 2016)
Dengue fever is an acute disease that clinically can cause death because there is no prediction system to estimate dengue fever cases so it resulted in the growing of dengue fever cases every year. Original data gathering in Jember area that uses technique of partial data gathering has caused data missing. To make this secondary data can be processed in prediction stage there is need to conduct missing imputation by using Monte Carlo method with four different randomization method, followed by data normality test with chi-square, then continued to regression stage. We use MSE (Mean Square Error) to measure prediction error. The smallest MSE result of regression is the best regression model for prediction.